The influence of climatic conditions of the harvest year on the wheat quality - Ruska, Banda; Anisoara, Camelia (Acta Agraria Debreceniensis, 2016)
Technological potential of wheat bread depends on the variety, manner and type of fertilizer, irrigation conditions and climatic conditions in their absence. This study was done on two varieties of wheat grown in Bihor county in a place with identical fertilization conditions, for two different years: year 2014 can be characterized by a greater quantity of rainfall during the wheat vegetation period and the year 2015 can be characterized by a drought during the growing wheat on the subject of the study. In the study was examined whether climatic conditions have any influence on the technological potential of wheat, not taking into account the data on quantity produced per hectare in the years studied.